If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (1 + 2w) * w * 2w = 40 Reorder the terms for easier multiplication: 2w * w(1 + 2w) = 40 Multiply w * w 2w2(1 + 2w) = 40 (1 * 2w2 + 2w * 2w2) = 40 (2w2 + 4w3) = 40 Solving 2w2 + 4w3 = 40 Solving for variable 'w'. Reorder the terms: -40 + 2w2 + 4w3 = 40 + -40 Combine like terms: 40 + -40 = 0 -40 + 2w2 + 4w3 = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(-20 + w2 + 2w3) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-20 + w2 + 2w3)' equal to zero and attempt to solve: Simplifying -20 + w2 + 2w3 = 0 Solving -20 + w2 + 2w3 = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| -60x^3+144x= | | c/4+85=99 | | 4x+1=6-x | | -4+6s+7m-4s-4m-6= | | 2(13-4x)-9(x+6)= | | 49x^2-91+42=0 | | -8x-(5x+5)=7 | | 2(h-4)=6 | | 3y+7(2y+6)-2+3(4y+9)=270 | | -7x-15=2x-6 | | 12a-11-9a=1 | | 7h-16=54 | | 3x^2+31x+8=0 | | 10=4+2d | | x(-11+x)=0 | | -4x+22=x-8 | | 2h-3=3 | | -40x^2-18x+36=0 | | 1=10-3t | | 22-x=4x-8 | | -8x^2+32x-30=0 | | 2r-4=4 | | 5X^2-66X+1=0 | | 41=15x+(-3)x^2 | | y=15+27x | | y=27x+15 | | 20u-12u=40 | | x^2-4-25=0 | | U+5=10 | | -3-7r=16 | | 3z=6 | | H=3v-b |